Seroprevalence of Helicobacter pylori in Bosnia and Herzegovina: a single-center cross-sectional study - Nejra Bektaš; Larisa Bešić; Aida Kulo Ćesić; Damir Marjanović; Jasminka Prguda-Mujić (Medicinski glasnik, 2026)
Aim: Many studies have demonstrated that over half of the World's population is infected with Helicobacter pylori (H. pylori). To evaluate the current H. pylori seroprevalence in Bosnia and Herzegovina (B&H), H. pylori antibodies (immunoglobulin G, IgG) from patients with suspected presence were analyzed. Methods: In total, 201/471 (42.7%) males and 270/471 (57.3%) females were enrolled between June 2024 and July 2024. They were tested using the enzyme-linked immunosorbent assay (ELISA) method. Results: The overall seroprevalence of H. pylori infection was 214 (out of 471; 45.4%) and did not differ in relation to sex. The seroprevalence rate of H. pylori was highest in the 50-69 age group, 81 (out of 137; 59.1%; 95% CI: 2.2-5.6), followed by the ?70 age group, 17 (out of 31; 54.8%; CI: 2.0-6.7), and the 30-49 age group, 101 (out of 219; 46.1%; 95% CI: 1.7-4.3). The lowest seroprevalence rate was in the younger age group (?29) with 15 (out of 84; 17.8%). Older age groups were more likely to be H. pylori positive and equivocal, while younger age groups negative for H. pylori infection. Conclusion: This single-center study is the first study providing information on the H. pylori seroprevalence in the B&H population and investigating its association with age and sex. Further research is needed to explore other risk factors and to develop effective ways to reduce the burden of this infection.
Keywords: Immunoglobulin G; ELISA; infection; population